A novel effort estimation approach for requirement changes during software development phase - Basri, Sufyan (Science and Engineering Research Support Society, 2015)
Managing software changes and achieving an effective change acceptance decision is one of the crucial factors in ensuring the software project success. Accepting too many changes will cause expense and delay and rejecting the changes may cause customer dissatisfaction. One of the inputs that help in achieving an effective change acceptance decision is by having reliable estimation on the change effort. From software development perspective, the estimation has to take into account the inconsistent states of software artifacts across project lifecycle i.e., fully developed or partially developed. These inconsistent states require different ways of estimation such as the fully developed artifacts may have different calculation compared to the partially developed artifacts. Many change effort estimation approaches have been developed and one of them is using impact analysis. One main challenge of this technique from software development perspective is that this technique is specifically used for software maintenance phase in which all software artifacts have been completely developed. This research introduces a new change effort estimation approach that is able to use different estimation techniques for different states of software artifacts. The outcome of this research is a new change effort estimation approach for software development phase using the extended version of the static and dynamic analysis techniques from our previous works.